PHYSICAL AND PSYCHOLOGICAL FACTORS AFFECTING SHOOTING PERFORMANCE IN FOOTBALL - Heru Yundridana; Ridho Bahtra; Asril; Nugroho Susanto; Ali Mardius (Curricula: Journal of Teaching and Learning, 2026)
Shooting accuracy represents a fundamental determinant of success in competitive football, relying heavily on a complex interaction between physiological capabilities and psychological readiness. Despite its importance, many training programs overlook the specific contribution of core stability and mental state. Consequently, this study aims to comprehensively analyze the influence of leg explosive power, stomach muscle strength, and self-confidence on the shooting ability of students at SSB Tuna Agung Salido. Understanding these relationships is crucial for developing targeted training protocols that maximize performance outcomes among young athletes. The research employed a quantitative approach with a correlational associative causal design, carried out in February 2026. The sample consisted of 28 students determined through a total sampling technique, ensuring all active members were included to represent the population accurately. Data collection instruments included the Standing Broad Jump test to measure leg explosive power, the sit-up test for stomach muscle strength, a standardized questionnaire for self-confidence, and a practical kick-to-target test for shooting ability. Data analysis was conducted using Path Analysis to determine direct and indirect effects between variables. Research results indicate that shooting ability is significantly influenced by both physical and psychological factors. Leg explosive power contributes 33.3% to shooting performance, while stomach muscle strength demonstrates a larger influence at 37.3%, highlighting the critical role of core stability in generating and transferring power during kicks. Self-confidence contributes 19.8%, underscoring the vital mental component of skill execution under pressure. No direct connection was found between leg explosive power and stomach muscle strength; however, both exert an indirect influence through self-confidence by 2% and 3% respectively. These findings confirm that an effective training program must simultaneously address physical strength and psychological factors to optimize students' shooting abilities. Coaches are advised to integrate core conditioning and mental resilience training alongside technical drills to ensure holistic development. Future research should explore additional psychological variables such as anxiety control to further refine training methodologies for youth football development.